PASTORAL KONSELING KERJA PADA HRD MANAGER YANG MENGALAMI STRESS KERJA - Melissa M.F Waturandang; Shanti N.C Ruata (Institut Agama Kristen Negeri Manado, 2021)
This study aims to describe pastoral work counseling for employees at PT IMS Manado who experience work stress. The method used is descriptive qualitative research method. The research subjects were employees at PT IMS Manado who experienced work stress and were given pastoral counseling assistance at work in the workplace. The results of the study show that employees who experience work stress are caused by poor interpersonal relationships which then result in decreased performance at work so that pastoral assistance is needed so that employees can understand themselves, others and God and His word. In the implementation of pastoral counseling, a confrontational counseling approach is carried out to confront clients directly with the problems they are facing and the problem solving that must be done.